The effects of peer tutoring and self-efficacy on math test anxiety. - Daban, Richelle Mae D.
This study examined the math test anxiety of participants as they were assigned to either low or high level of self-efficacy and whether they belong to the group with peer tutoring or without. It also examined the interaction effect between the high and low levels of of self efficacy and the groups of peer tutoring as regards to math anxiety. The participants were First Year college students of the University of the Philippines in the Visayas, Miag-ao, Iloilo, enrolled in a Math 11 course (College Algebra) for the Second Semester, Academic Year 2000-2001. The Math Self-efficacy Scale was given to the participants to determine their self-efficacy level. Fifty percent of the participants in the high self-efficacy level were assigned to the group with peer tutoring and the other fifty percent were assigned to the group without peer tutoring. This procedure was also done to the low self-efficacy level. In order to determine the Math test anxiety of participants, the Math Test Anxiety Scale was given. A 2 ( levels of self-efficacy X 2 (peer tutorialgrouping) ANOVA was used to determine if there are any significant differences in the math test anxiety of the low and high self-efficacy, and the math test anxiety of with and without peer tutoring groups. This statistical tool was also used to depict any interaction effect between the math test anxiety of low and high self-efficacy and with or without peer tutoring groups. It was found that there was a significant main effect for self- efficacy, F (1,60)= 22.31, p_<0.01 and no significant main effect for peer tutoring, F (1,60)=3.27, p_>0.05. There was no significant effect, F (1,60)=2.09, p_>0.05. This means that self-efficacy has an effect on math test anxiety. Peer Tutoring had no effect on math test anxiety and the interaction of both self-efficacy and peer tutoring had no effect as well on math test anxiety.